INCORPORATING NEXUS ECOLABELS INTO HOUSEHOLD LEVEL FOOD WASTE MITIGATION STRATEGIES – ENVIRONMENTAL PERSPECTIVES FROM LIFE CYCLE ASSESSMENT: Enhancing Sustainability Through Ecolabeling: Evaluating Environmental and Economic Impacts in Food Waste Reduction Using JRC FW Calculator - Kitanovski, Vladimir (Journal on Processing and Energy in Agriculture, 2025)
This study provides a comprehensive evaluation of the economic and environmental ramifications of food waste reduction through the implementation of Smart NEXUS Ecolabels. Employing the JRC Food Waste Prevention Calculator, the analysis centers on a medium-case scenario wherein household food waste is curtailed by 20%. The results reveal that mitigating food waste at this scale yields substantial benefits, with each ton of food waste prevented equating to the conservation of approximately 78 meals, reduction of 323 kg CO₂ equivalent emissions and an estimated cost savings of 133 euros in production and waste management expenditures. Extrapolating these findings to the EU’s aggregate annual food waste, the potential large-scale impact is profound, encompassing 4.6 billion meals saved, 19.1 million metric tons of CO₂ equivalent emissions mitigated, and an estimated economic benefit of 7.85 billion euros. The environmental impact assessment, conducted across 16 midpoint categories, underscores the pivotal role of targeted food waste prevention strategies in curbing pollution, conserving natural resources, and bolstering food security. These findings substantiate the transformative potential of Smart NEXUS Ecolabels in facilitating systemic reform, reinforcing the necessity of embedding food waste reduction measures within broader sustainability frameworks to enhance resource efficiency at scale.